DOCUMENTING, RESEARCHING AND PROMOTING URBAN HISTORY IN UKRAINE: EXPERIENCES OF THE CENTER FOR URBAN HISTORY IN LVIV (City: History, Culture, Society, 2019)
The article presents establishing and developing the Center for Urban History in Lviv as a part of the larger trend to promote and institutionalize urban history and urban studies in Ukraine and Eastern Europe. Discussing founding ideas and program, as well as their further implementation gives an insight into academic as well as public landscapes of urban research, both locally and internationally. The Center was founded in 2004 as a private foundation in Vienna and two years later, in 2006, the office was established in Lviv to launch its program activities. Major objectives of the Center are to promote research on the history of cities and towns in Eastern and Central Europe; to advance urban history as an interdisciplinary field and a platform for international cooperation; to enhance critical understanding of urban history and heritage in cooperation with local and international institutions; to engage into contemporary cultural life in the city and thus contribute to public and open engagement with the past. Three major focuses of work of the Center were gradually shaped and now they include research, digital archiving, digital and public history.While initially many projects focused on Lviv, expanding geographical scope was part of the development of the institution.Therefore, presently, the interests include various urban experiences, such as of historical cities, Soviet cities, industrial and mono-industrial, multiethnic cities, as well as the cities surviving conflicts and violent transformations. Over the 10 years of its activities, the Center has become both the institution to conduct research and an instrumental actor to transform symbolic spaces of Lviv, the place for discussions and presentation of results of other studies and initiatives, a platform for informal educational practices and a laboratory to develop new ways of contextualizing, representing and using different archival media and  documents. Different formats such as schools, conferences, workshops, seminars, lectures, presentations and round tables, exhibitions, interactive maps, digitalization and promotion of collections of photo and video materials, and educational programs for children and adults constitute our program activities and help engaging broader academic and non-academic audiences into a dialogue to promote participatory historical culture in Ukraine.
Keywords: Center for Urban History; digital archives; digital history; public history; media archive; Lviv; interdisciplinarity; educational platform